Factors That Influence The Incidence Of Low Birth Weight - Saputro, Heri; Supraptini, Supraptini (Open Access Health Scientific Journal, 2024)
Background: The causes of the birth of Low Birth Weight (LBW) babies vary greatly, many references state that it is related to maternal hypertension, maternal nutritional status, maternal age and the number of previous births the mother has had. This research aims to determine the relationship between factors that influence LBW and the incidence of LBW. Method: This research uses an analytical survey with a cross sectional approach. The number of research participants was 80 postpartum mothers who were taken using a simple random sampling technique. Data analysis was carried out using regression logistics. Result: The results of statistical analysis using the logistic regression test showed that there was no significant relationship between nutrition (0.101), age (0.447) and parity (0.681). The results of logistic regression analysis showed pregnancy hypertension (p=0.000). There is a relationship between pregnancy hypertension and low birth weight. Conclusion: The research results showed that pregnancy hypertension is the dominant factor in the incidence of LBW so that during pregnancy it is hoped that pregnant women can control pregnancy hypertension with pharmacological or non-pharmacological therapy.